2016
DOI: 10.1371/journal.pone.0152808
|View full text |Cite
|
Sign up to set email alerts
|

Specific Induction of TSLP by the Viral RNA Analogue Poly(I:C) in Primary Epithelial Cells Derived from Nasal Polyps

Abstract: IntroductionChronic rhinosinusitis with nasal polyposis is an inflammatory disease that, although not directly linked to allergy, often displays a Th2-skewed inflammation characterized by elevated local IgE and IL-5 levels. The nasal cavity is constantly exposed to bacteria and viruses that may trigger epithelial inflammatory responses. To gain more insight into mechanisms by which such a biased inflammation might arise, we have investigated the epithelial expression of the Th2 skewing mediators (TSLP, IL-25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Moreover, previous studies revealed that the expression of TSLP was induced by poly(I:C) in nasal epithelial cells of NP. 27 Thus, we tested whether the IL-22/IL-22Ra1 axis could promote TSLP expression under poly(I:C) stimulation. NHBE cells stimulated with IL-4, IL-13, or IL-22 alone did not promote TSLP production ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous studies revealed that the expression of TSLP was induced by poly(I:C) in nasal epithelial cells of NP. 27 Thus, we tested whether the IL-22/IL-22Ra1 axis could promote TSLP expression under poly(I:C) stimulation. NHBE cells stimulated with IL-4, IL-13, or IL-22 alone did not promote TSLP production ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[49][50][51] A general knockdown of the T2 inflammatory axis is seen. 44 Viral rhinitis is a potent drive for CRSwNP 52 and omalizumab may prevent viral immune amplification of inflammatory pathways in CRSwNP. An important and novel finding with omalizumab treatment is improvement in innate viral defence.…”
Section: Mechanism Of Omalizumabmentioning
confidence: 99%
“…TSLP and TSLP receptor have been found highly expressed in sinus mucosa of patients with CRSwNP [811], and a recent work by Golebski et al [22] was able to demonstrate that the TLR3 agonist and viral analog poly(I:C) were able to induce higher TSLP mRNA and protein expression in the epithelium isolated from nasal polyposis patients compared to epithelium form healthy controls, while a few and contrasting observations have been reported on the presence of IL-25 in CRS. IL-25 mRNA has been reported to be significantly elevated in ethmoid sinuses of CRSwNP compared to controls and CRSsNP by Lam et al [23].…”
Section: Discussionmentioning
confidence: 99%